Analisis Leverage dan Pertumbuhan Perusahaan: Studi Pada Bank Rakyat Indonesia Persero, Tbk. yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018 - Merisa Oktaria; Rinto Alexandro; Windy Utami Putri; Fendy Hariatama; Dedy Dwi Ervansyah; Hendrowanto Nibel; Nonsihai Nonsihai; Susi Sukarningsi (FKIP, Universitas Palangka Raya, 2022)
The increasingly fierce competition in the business world, requires companies including banks to develop strategies in running their business. This strategy aims to create competitive advantage, growth and development of the company. This also happens in the banking world, therefore the author wishes to analyze Leverage and Company Growth at PT. Bank Rakyat Indonesia Persero, Tbk. This research is a type of descriptive research, the object of this research is the financial statements of PT. Bank Rakyat Indonesia (Persero), Tbk in 2014-2018 and this study uses quantitative and qualitative data types derived from the company's financial statements as qualitative and quantitative data types. The data collection technique in this research is through documents related to and supporting this research, namely the Financial Statements of PT. Bank Rakyat Indonesia (Persero), Tbk. listed on the Indonesia Stock Exchange (IDX) in 2014-2018. In this study, the data analysis technique used is through trend analysis assisted by graphs. The results showed that the DER of PT. Bank Rakyat Indonesia (Persero), Tbk. For 5 years (2014-2018) it was 630,722 (720.52 + 676.49 + 583.62 + 573.00 + 599.98 : 5) or 6.3%, which means PT. Bank Rakyat Indonesia (Persero), Tbk. has sufficient capital of its own which is used to pay debts systematically. Growth of PT. Bank Rakyat Indonesia, Tbk. From 2014 to 2018 it tends to fluctuate. If seen in 2015 there was a significant decline in Bank BRI's profit growth from the previous year. This happened because of the economic conditions that occurred, namely in 2014 the percentage of BRI's credit reached 17.2%, but it turned out that in 2015 there were bad loans which ultimately suppressed BRI's profit in 2015. In general, the growth of BRI Bank in 2014-2018 was quite good because every year it always gives an increase of almost always double digits (percentage) except in 2015 which only rose 9.54% but this is reasonable because it has reasons that are in accordance with the economic conditions faced